2011
DOI: 10.1007/s00384-011-1362-x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic bowel wall thickening: Is there a need for endoscopic evaluation?

Abstract: Colonic bowel wall thickening is not a common finding on CT scan in this study. Consequential endoscopic evaluation was performed in less than 50% of patients. Pathological findings were detected in 80% of these patients. We recommend endoscopical evaluation if bowel wall thickening is reported on CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…When the colon is inflated, the wall thickness is less than 3 mm [19]. In CT taken under optimal conditions, the thickness of the colonic wall is considered normal up to 3 mm and pathological above 5 mm [8]. Colonic redundancy with solid-liquid stool makes it difficult to measure wall thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the colon is inflated, the wall thickness is less than 3 mm [19]. In CT taken under optimal conditions, the thickness of the colonic wall is considered normal up to 3 mm and pathological above 5 mm [8]. Colonic redundancy with solid-liquid stool makes it difficult to measure wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the use of colonoscopy in patients with CWT based on CT results [5,6]. Some advocate colonoscopy for these patients [7,8] while some recommend colonoscopy only for the risky group [2,9]. The American Gastroenterology Association still does not accept CWT as an absolute colonoscopy indication [1].…”
Section: Introductionmentioning
confidence: 99%
“…The bowel wall thickening could be a manifestation of underlying inflammatory, infectious, ischemic, or neoplastic pathology or may represent normal findings because of technical reasons, such as inadequate distension of the bowel. Previously, the significance of colonic wall thickness was evaluated by various studies, and most of the studies have concluded that patients with colonic wall thickness on CT should undergo colonoscopy and biopsy as a majority of these patients will have an underlying disease . This recommendation of endoscopy has been made because of the increased risk of neoplastic diseases in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the significance of colonic wall thickness was evaluated by various studies, and most of the studies have concluded that patients with colonic wall thickness on CT should undergo colonoscopy and biopsy as a majority of these patients will have an underlying disease. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This recommendation of endoscopy has been made because of the increased risk of neoplastic diseases in the colon. However, the significance of ileocecal wall thickening on CT has been infrequently evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence in the literature with many studies advocating for endoscopic evaluation in all cases due to high rates of pathology [12][13][14] while some studies in the literature suggest that only patients deemed at an increased risk need endoscopic evaluation [15]. In addition to this, some studies in the literature attempt to delineate benign from malignant causes of MT [16].…”
Section: Introductionmentioning
confidence: 99%